2011
DOI: 10.1007/s00382-011-1152-8
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime extratropical cyclone frequency around Japan

Abstract: Data analysis and regional atmospheric model (RAM) experiments revealed key factors in the control of wintertime cyclone passage routes from Northeast Asia to the western North Pacific. The cyclone routes were independent of the global flow pattern in the interannual variability, while cyclone growth closely agreed with linear baroclinic theory. The RAM experiments with a different lateral boundary condition composed of a combination of monthly mean and transient components also showed that the upstream eddies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…We obtained an increasing trend in the cyclone growth rate and the number of explosive cyclones east of Japan, which was probably associated with the increase in lowlevel baroclinicity and the increase in humidity. This result is consistent with the enhancement of storm-track activity found in a global warming experiment (Inatsu and Kimoto 2005). Moreover, the result is also consistent with Nakamura et al (2002), although the significant weakening of the East Asian monsoon suggested in their study was not identified in this study.…”
Section: Summary and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We obtained an increasing trend in the cyclone growth rate and the number of explosive cyclones east of Japan, which was probably associated with the increase in lowlevel baroclinicity and the increase in humidity. This result is consistent with the enhancement of storm-track activity found in a global warming experiment (Inatsu and Kimoto 2005). Moreover, the result is also consistent with Nakamura et al (2002), although the significant weakening of the East Asian monsoon suggested in their study was not identified in this study.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…The same analysis for other seasons showed that the increase was most prominent in winter. This result is consistent with the recent enhancement in storm-track activity during winter over the northwestern Pacific (Nakamura et al 2002;Inatsu and Kimoto 2005), although the storm-track enhancement was reported for much broader areas.…”
Section: B Changes In Explosive Cyclone Frequencysupporting
confidence: 93%
See 1 more Smart Citation
“…Another example is the strengthening of the extratropical cyclones passing through Taiwan, the southern coast of Japan, and the Northwest Pacific southeast of Japan (called Nangan cyclones in Japan). Recently, Inatsu and Terakura (2012) demonstrated that the growth rate of the Nangan cyclone is controlled by the background mean flow through baroclinic instability. As the Nangan cyclone passage route starts around Taiwan, intensified vertical shear due to global warming may increase the growth rate of the Nangan cyclone in the late 21st century.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Up to now, not much attention has been given to the effects of this uncertainty on RCM simulations, which may become even more pronounced with increasing difference between the coarse and fine resolutions. Efforts towards tracking weather systems, and more specifically extratropical cyclones, have been already made by generating RCM ensemble simulations with modified lateral boundary conditions from reanalysis data (Inatsu and Terakura, ). Using driving data from different GCMs does not solve this issue since GCMs may provide atmospheric fields where weather patterns differ significantly from one to the other.…”
Section: Introductionmentioning
confidence: 99%